World Development Report 1980 - World Bank (New York: Oxford University Press, 2012)
Developing countries start the decade facing two major challenges: to continue the social and economic progress of the past 30 years in an international climate that looks less helpful; and to tackle the plight of the 800 million people living in absolute poverty, who have benefitted too little from past progress. This report examines some of the difficulties and prospects in both areas. One of its central themes is the importance of people in development. The first part of the report addresses the expected sluggish world economic growth as oil-importing countries reduce their current account deficits and adapt to higher energy costs. Domestic policies of developing countries will be crucial, and the fate of poor people in these countries will be decided largely by domestic opportunities and policies. The second part of the report describes the role of human development programs (in education, health, nutrition, and fertility reduction) and their related effects on productivity and population growth.